ADVANTAGES OF MINIMALLY INVASIVE SPINE SURGERY FOR THE TREATMENT OF THORACOLUMBAR FRACTURES: A SYSTEMATIC REVIEW - Arfan Surya Adhitama; Rieva Ermawan (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Thoracolumbar spine fractures are the most common vertebral fractures. Trauma to the thoracolumbar spine can cause disability, spinal deformity, neurological deficits, psychological, economic and social problems. Safe and effective treatment is very important. Currently, the miss approach is only used for the management of type A (AO classification) and stable thoracolumbar fractures. Objective: this systematic review aims to determine the advantages of using the miss approach compared to the open approach in the treatment of thoracolumbar fractures. Method: Using a systematic review method, this study searches for literature that matches the criteria in the PubMed electronic database and the wiley online library. There are 644 samples (290 samples of the MISS approach and 354 samples of the open approach) from seven articles that match the criteria that we have determined. Next, we extract data from our entire sample to find out the advantages of the MISS approach.                        Results: The MISS approach provides advantages in intraoperative (reduced operating time and blood loss) and early postoperative (reduced VAS score and hospitalization). In addition, the MISS approach also has advantages in the form of: minimal CSA, low transfusion requirements, and has a good ODI score. After more than one year of follow-up, the miss approach had the same neurologic recovery and risk of complications as the open approach. Conclusion: A minimally invasive approach provides an advantageous and safer to the management of all types of thoracolumbar fractures. Keywords: Advantage, Minimally Invasive, Open Surgery, Thoracolumbar Injuries